Peran Komite Sekolah dalam Meningkatkan Mutu Pendidikan Agama Islam (PAI) di SDN Sukamanah 01 Kecamatan Megamendung Bogor - Indah Sekar Hati; Nadjematul Faizah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
The background of this research was since the writer finished her study in SDN Sukamanah 01 until studying in Institute For Quranic Studies Jakarta, the number of school committee members is only one person, therefore it encouraged the writer to conduct research of why SDN Sukamanah 01 did not add another member of school committee in line with the regulation of Republic of Indonesia Minister of Education and Culture Number 75 Year 2016 which stated that school committee members should have minimum five persons. The aim of this research is to describe School Committee’s Roles in Improving Quality of Islamic Religion Education in SDN Sukamanah 01 Kecamatan Megamendung Bogor. Qualitative method is used in this research. Besides, the data collection techniques used interview, observation and documents. This research is an descriptive analysis. The result of this research showed that school committee’s role in improving quality of education in SDN Sukamanah 01 was not optimum due to some circumstances. They are the number of school committee was only one person, the committee did not always stay in school. It was caused by other responsibilities beyond as a committee in the school. In addition, school committee’s role as a considerator was not good enough. In fact the school committee did not see the situation in the school so that school committee always agreed anything that principal reported. Quality of Islamic Religion Education in SDN Sukamanah 01 was good enough eventhough the school committee did not give full advices. This was shown through students’ result of average scores of School Final Test (UAS) 2019 which above average.